Analysis of the environmental impacts of Precabura Lagoon: a proposal for sustainable management - Pinheiro, Samuel Tavares; Júnior, Antonio Ferreira Lima; Costa, Maria Clélia Lustosa (Revista Hipótese, 2017)
In order to identify the environmental impacts present in the Precabura lagoon and its surroundings, it was analyzed the forms of land use and occupation. From the integrated analysis, it was possible to characterize environmental potencials and limitations, and note possible weaknesses due to the inordinate use. Located between Fortaleza (national metropolis) and Eusébio, the lagoon suffers from the absence of public management’s action, therefore it’s propose to mitigate measures capable of fostering economic and social development in balance with environmental quality.